Potensi Ekonomi Kota Cirebon Untuk Menunjang Kawasan Rebana - Rachman, Nazwah Syakira; Ningrum, Sinta (stiatabalong.ac.id, 2025)
The primary objective of this research is to examine the role of regional development in fostering regional competitiveness and enhancing community welfare. The impetus for this study stems from the observation that Cirebon City, despite its status as the Core Urban Area in the Rebana Region, is exhibiting suboptimal performance in terms of economic growth. This is evidenced by its lower economic growth rate of 5.01%, which stands in contrast to the Rebana Region average of 5.81%. The research employed a descriptive quantitative approach, utilizing primary data from in-depth interviews with Bappelitbangda and DKUKMPP Cirebon City, along with secondary data from government documents and BPS.The analysis was conducted using a combination of Location Quotient, Shift Share Analysis, and Klassen Typology methods, guided by the Local Economic Development (LED) framework. The findings indicate that Cirebon City's economy is predominantly driven by eight key sectors, namely transportation, warehousing, and accommodation-food and beverage. However, the trade sector, which is the primary contributor to the GRDP, is exhibiting signs of decline.This study proposes a methodological framework for analyzing leading sectors and offers recommendations for implementing potential-based regional economic development strategies. These recommendations can inform the formulation of metropolitan area development policies in Indonesia.